Evaluation of corrosion of steel embedded in concrete exposed to carbonation AAS using a factorial experiment with repeated measures. (2013)
This article presents various techniques for assessing corrosion, the linear polarization resistance and galvanostatic pulse, the analysis was performed using analysis of variance models using a factorial experiment with three factors, one repeated measure, because on the same experimental unit (reinforced concrete), it experienced several samples to be measured in time (0 h=1, 350 h=2, 700 h=3, 1050 h=4, 1700 h=5 y 2600 h=6). This makes the observations are not independent, the other two factors relate to, the binder (ce: 1 = activated slag [AAS] and 2 = ordinary Portland concrete [OPC]) and the exposure condition (ca: 1 = y 2 = environmental exposure accelerated carbonation). These factors were discussed according to the results of the electrochemical properties. Initially performed the statistical processing of each of the variables in relation to the properties and analyzed the interaction between them. Where they established the differences in materials used as coating steel, concrete, OPC and AAS. OPC concrete specimens, exhibited a resting potential, polarization resistance and ohmic (CO2 condition) than those obtained for reinforced concrete in AAS.